Efeito do etanol no crescimento de bactérias lácticas - Estevinho, Leticia M. (2011)
Neste trabalho foi estudado o efeito do etanol no crescimento-taxa de crescimento, duração da fase lag e produção de biomassa total (medida em absorvância a 600 nm)- de espécies do género Leuconostoc, Pediococcus e Lactobacillus, isoladas de vinhos. This study deals with the effect of ethanol on the growth rate, lag phase and biomass production by several strains classified under the genera Leuconostoc. Pediococcus and Lactobaciflus. Low concentrations of ethanol significantly increased the growth rate of all strains, which intensity was variable with the pH and among the strains. The repressive effect of ethanol, at higher concentrations, on the bacterial growth was more relevant in Leuconostoc than with Lactobaciflus and Pediococcus. Besides, this effect was significantly dependent of the initial pH of the culture medium.